Vibrationally resolved structure in O+2 dissociation induced by intense ultrashort laser pulses - Zohrabi, M.; McKenna, J.; Gaire, B.; Johnson, Nora G.; Carnes, K. D.; De, S.; Bocharova, I. A.; Magrakvelidze, M.; Ray, D.; Litvinyuk, I. V.; Cocke, C. L.; Ben-Itzhak, I. (My University, 2011)
Laser-induced dissociation of O+2 is studied in the strong-field limit using two independent methods, namely a crossed laser–ion-beam coincidence 3D momentum imaging method and a supersonic gas jet velocity map imaging technique (790 and 395 nm, 8–40 fs, ~1015 W/cm2). The measured kinetic energy release spectra from dissociation of O+2 and dissociative ionization of O2 reveal vibrational structure which persists over a wide range of laser intensities. The vibrational structure is similar for O+2 produced incoherently in an ion source and coherently by laser pulses. By evaluation of the potential energy curves, we assign the spectral energy peaks to dissociation of the v=10–15 vibrational states of the metastable a4Πu state via the dissociation pathway ∣∣a4Πu⟩→∣∣f4Πg−1ω⟩—a mechanism equivalent to bond softening in H+2.